THE RELATIONSHIP BETWEEN BLOOD PRESSURE LEVELS AND THE INCIDENCE OF DIABETIC NEUROPATHY IN TYPE-2 DIABETES MELLITUS PATIENTS. - Indriyani, Putri; Yuliyanasari, Nurma; Kartikasari, Irma; Irfana, Laily (Biomedika, 2025)
Diabetic neuropathy (DN) is microvascular complications in people with type 2 diabetes that can significantly affect patients’ quality of life. Higher levels of blood pressure are known to be associated with an increased occurrence of diabetic neuropathy in type 2 diabetes patients. This study aimed to determine the risk factors for blood pressure levels with the incidence of diabetic neuropathy. This approach used purposive sampling with a cross-sectional methodology. SPSS version 26 with the chi square test was used to analyze the data. This study involved 68 patient. Patient with diabetic neuropathy mostly female (23.8%), aged of 51-60 years (16.2%), have had diabetes for > 5 years (22.1%), consumed insulin or anti-diabetic medications orally (35.5%), have a history of hypertension (20.6%), and do not take antihypertensive drugs (20.6%). ccording to the findings of the ci-squre analysis, there was a significant correlation between the incidence of diabetic neuropathy and the level of blood pressure (p < 0.04). Patients who suffer from neuropathy diabetic had the most hypertension grade 1. Meanwhile, patients who do not had diabetic neuropathy mostly have optimal, normal and normal-high blood pressure. In conclusion, there is a correlation between the incidence of blood pressure levels and diabetic neuropathy.